What is the Level of Knowledge of Birth Control among Women of Reproductive Age in Bwaise Slum? A Cross-Sectional Study. - Muderhwa Bacigale, Rodrigue (Student's Journal of Health Research Africa, 2022)
Background The need to control childbirth and maintain a manageable family size is a fact of modern life. This is because of the social and economic realities of the modern world system. Because of this, the practice of contraception has remained in the spotlight. To increase birth control uptake, knowledge and awareness are frequently used. However, evidence on birth control knowledge among populations in low socioeconomic settings in Africa is limited. The goal of this research was to look into women's knowledge of birth control options in the Bwaise slum. Methodology Using a cross-sectional study design, we interviewed 384 women aged 15–49 years, selected through systematic random sampling. Data on socioeconomic characteristics, knowledge of birth control options, and birth control use were collected using a structured questionnaire. Descriptive and inferential statistics (chi-square set at 0.05 level of significance) analysis were done using IBM SPSS version 21. Results The mean age of participants was 29.39 years. There is a high level of knowledge and awareness of birth control options but with relatively low uptake, 91.4% of women knew at least one option. 66.4% of respondents reported using any birth control options in the past compared to 37.2% currently using. Injectable, oral pills and Norplant/implant were the most known and used options. Age, level of education, marital status, and income were significantly associated with the use of birth control (p< 0.05). Conclusion and recommendation Our findings show that respondents have high knowledge of birth control but low use. We, therefore, recommend that government health agencies conduct a sensitization campaign aimed at the increase in the utilization of birth control services involving religious and cultural leaders. Women of reproductive age, to attend at least one SRH counseling session, in any health facility, to be updated with relevant news on birth control services.